How have Europe’s outermost regions dealt with the economic and social consequences of the COVID‐19 crisis? Effects, policies and recommendations - Bourdin, S.; Cottereau, V.; Hermet, F.; Jean‐Pierre, P.; Medeiros, E. (Regional Science Policy and Practice, 2023)
This paper contributes to the literature by documenting how regions have experienced and managed the coronavirus disease 2019 (COVID-19) crisis, particularly for regions that are largely understudied and whose territorial characteristics (related to hyper-remoteness and poverty) deserve greater attention. To this end, the study investigated regional strategy and planning documents and conducted 32 semi-structured interviews with public authority representatives, sectoral actors and civil society groups. The findings show the socio-economic consequences of the crisis and local policy responses. The study proposes a reflection in terms of public policies on what could be the ‘world after’ in the outermost regions, and highlights how the COVID-19 crisis presented an opportunity to design and implement future territorial development policies that are more adapted to the context and territorial characteristics of these regions. Building a resilience policy in the outermost regions requires strengthening the territories’ capacities, which involves their structural equipment.